Pendampingan Analisis Peluang Bisnis Makanan Sehat Berbasis Business Model Canvas pada Mahasiswa Kewirausahaan - Windi Yearli; Shifa Nazma Zakkiyatul Adawiyah; Suci Hidayanti (Niswantara: Jurnal Pengabdian Kepada Masyarakat, 2026)
The increasing awareness of healthy lifestyles has transformed consumption behavior, creating significant opportunities in the healthy food business sector. However, students often face limitations in designing systematic and sustainable business models. This community service activity aims to assist students in analyzing business opportunities in the healthy food sector using the Business Model Canvas (BMC) approach. The method employed is participatory, consisting of socialization, training, hands-on BMC development, and evaluation stages. The results indicate that participants successfully understood the nine elements of BMC and were able to apply them in designing relevant and market-oriented healthy food business models. This activity contributes to enhancing students’ entrepreneurial literacy and fostering innovative and sustainable business ideas.